Pengaruh Kualitas Pelayanan, Fasilitas Dan Lokasi Terhadap Keputusan Menginap Di Hotel Graha Dinar Bogor - Nurul Arifiyani; Lucky Hikmat Maulana; Samsuri (KARIMAH TAUHID, 2022)
ABSTRACT Competition in hotel companies requires companies to be able to overcome the competitive market climate by focusing on marketing such as planning products, setting prices, promoting and distributing goods and services that can meet consumer needs. The purpose of this research is to find out how the quality, hotel facilities and location are simultaneously and partially in purchasing decisions at the hotel. Questionnaires were distributed to 95 consumers, using probability sampling technique (sample random sampling). The type of research used is qualitative and quantitative methods with survey methods that are descriptive or verification and use multiple linear regression analysis methods. The results showed that the quality of service, facilities and location simultaneously and partially have a positive and significant effect on purchasing decisions. Hotel Graha Dinar Bogor should further improve the quality of services, facilities and locations so as to increase company revenue by providing regular maintenance on the building, providing training to employees, adding room types, coloring wall paints that are in line with the theme in each room, maintaining existence hotels, providing information on licensing government regulations, increasing the products offered such as swimming pool facilities, playgrounds and others and increasing promotions at hotels, especially in the field of advertising. Keywords: Service Quality, Facilities, Location and Purchasing Decisions